AN EPIDEMIOLOGICAL STUDY OF ALUMINIUM PHOSPHIDE POISONING AT ALLAHABAD. (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
During one-year study period, out of a total 13,100 admissions, 301 suspected poisoning cases (2.3%) were   admitted to the Swarup Rani Nehru Hospital, Allahabad. 120 poisoning cases (39.9%) were recorded in the  summer season (March to June) and 235 (78.1%) were in the age group of 11-30 years. Male to female ratio  was 2:1. Out of 204 males, 136 belonged to the rural area and 56 to the urban area, while in 13 cases, residential status could not be traced.  Out of the 1752 medicolegal autopsies conducted during the study period in the mortuary, 205 were suspected poisoning deaths and 83 of these were circumstantially established cases of aluminum phosphide poisoning. Most vulnerable age group was 21-30 years accounting for 40.5% of poisoning deaths. Male female ratio was  2:1. Maximum incidence of poisoning deaths was observed in the rainy season (41.95%). 61.5% of victims were of rural background.  On gross examination, almost all vital organs were found to be congested. A variety of microscopic changes were observed in different organs. Easy availability of this cheap, highly toxic substance was responsible for an increased incidence of aluminum phosphide poisoning or deaths.
Keywords: gross examination; admissions